Revision of Neotropical Cariocamyia Snyder (Diptera: Muscidae), including first description of male of Cariocamyia vibrissata (Stein) - Ramos-Pastrana, Yardany; Córdoba-Suarez, Eric; Gomes, Lucas R. P. (Zootaxa, 2026)
Cariocamyia Snyder, 1951 is a Neotropical genus of Cyrtoneurininae (Diptera: Muscidae) with two known species from Brazil and Colombia. Here, we redescribe both Cariocamyia species, including the first male description of Cariocamyia vibrissata (Stein, 1918), as well as images of the male and female habitus, images of the holotype habitus, and drawings of the male and female terminalia. Additionally, we present an updated distributional map and an identification key, and provide a brief discussion of the morphology of both species.